A study of labile natural products occurring in Salsola tuberculatiformis Botsch. (Boraginaceae) - Maritz, M.(Matilda) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1994.